Sculptures of Parvati and Ganesha with a Nandi - Temples of India Project Team (Jio Institute, 2024)
In front of the entrance to the mulaprasada (main temple) inside the complex, there is a platform with ancient stone sculptures of a goddess (probably Parvati), Ganesha (covered in vermilion) and a small Nandi. Another Nandi figure, bigger in size, is placed directly in front of the temple.